Go Negosyo: Joey Concepcion's 100 Inspiring Stories of Small Entrepreneurs: Tagumpay mula sa kahirapan - Concepcion, Joey (Manila, 2010)
Go Negosyo presents 100 stories of inspiration from all over the country. Learn how these entrepreneurs triumphed and never gave up despite the burdens and trials that would have beaten others and weaker character.
Keywords: Entrepreneurship; Small Business - Philippines